2010
DOI: 10.1007/s10533-010-9427-4
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated microbial organic matter mineralization following salt-water intrusion into tidal freshwater marsh soils

Abstract: The impact of salt-water intrusion on microbial organic carbon (C) mineralization in tidal freshwater marsh (TFM) soils was investigated in a year-long laboratory experiment in which intact soils were exposed to a simulated tidal cycle of freshwater or dilute salt-water. Gas fluxes [carbon dioxide (CO 2 ) and methane (CH 4 )], rates of microbial processes (sulfate reduction and methanogenesis), and porewater and solid phase biogeochemistry were measured throughout the experiment. Flux rates of CO 2 and, surpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
197
6
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(226 citation statements)
references
References 65 publications
21
197
6
2
Order By: Relevance
“…2a and c). Similarly, other studies have documented short-term increases in potential CO 2 production, CO 2 emissions, and/or the production of dissolved inorganic C following saltwater intrusion (Chambers et al, 2011Weston et al, 2011;Marton et al, 2012;Jun et al, 2013), with the duration of the response being < 3 weeks (Chambers et al, 2011) up to 6 months (Weston et al, 2011). In contrast, short-to moderate-term saltwater intrusion typically results in decreased rates of CH 4 production and emissions, which also occurred in our study ( Fig.…”
Section: Initial Biogeochemical Effects Of Saltwater Intrusionsupporting
confidence: 88%
See 1 more Smart Citation
“…2a and c). Similarly, other studies have documented short-term increases in potential CO 2 production, CO 2 emissions, and/or the production of dissolved inorganic C following saltwater intrusion (Chambers et al, 2011Weston et al, 2011;Marton et al, 2012;Jun et al, 2013), with the duration of the response being < 3 weeks (Chambers et al, 2011) up to 6 months (Weston et al, 2011). In contrast, short-to moderate-term saltwater intrusion typically results in decreased rates of CH 4 production and emissions, which also occurred in our study ( Fig.…”
Section: Initial Biogeochemical Effects Of Saltwater Intrusionsupporting
confidence: 88%
“…This response is supported both by thermodynamic theory (i.e., sulfate reduction is energetically favorable over methanogenesis) (Schlesinger, 1997) and the experimental results of several other saltwater intrusion studies (e.g., Weston et al, 2006;Chambers et al, 2011;Marton et al, 2012;Morse et al, 2012;Neubauer, 2013a). However, Weston et al (2011) reported contrasting results, and documented a large, sustained increase in CH 4 emissions that persisted for 5 months following simulated saltwater intrusion. One proposed explanation for this inconsistency is that soil characteristics or other site properties may mediate system responses to saltwater intrusion.…”
Section: Initial Biogeochemical Effects Of Saltwater Intrusionmentioning
confidence: 61%
“…5). These simple comparisons do not include important long-term constraints on the concentration of carbon within a wetland soil (Kirwan and Mudd, 2012), changes in carbon quality (Ball and Drake, 1997), interactions between multiple components of global change (Langley and Megonigal, 2010) or various feedbacks between climate, biota, and sea-level rise (Wolf et al, 2007;Weston et al, 2011;Kirwan and Mudd, 2012). How temperature sensitivities of labile carbon decomposition relate to the more refractory carbon that is important for long-term carbon burial, is poorly understood (Fang et al, 2005;Craine et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the freshwater sediments used in this simulation had lower sulfate availability, and the sulfatereducing bacteria abundances were an order of magnitude lower than methanogens. In some cases, however, sulfate reduction can increase without a corresponding decrease in CH 4 production (Hopfensperger et al, 2014), especially if seawater intrusion increases both sulfate and organic matter availability (Weston et al, 2011).…”
Section: Seawater Addition Experimentsmentioning
confidence: 99%